Message forwarding for WSN-Assisted Opportunistic Network in disaster scenarios. (1st July 2019) - Fu, Xiuwen; Yao, Haiqing; Postolache, Octavian; Yang, Yongsheng
Abstract: Existing opportunity networks can hardly satisfy the requirements of disaster scenarios for low-latency messaging. Due to this reason, we develop a new opportunistic network framework WAON (WSN-Assisted Opportunistic Network). Owing to the easy-deployment and self-organizing features of wireless sensor networks (WSNs), WAON has obvious advantages in disaster scenarios. In order to make better use of the messaging capability of WAON and provide low-latency messaging services in disaster scenarios, this paper proposes a forwarding mechanism NetSpray for WAON, which supports four forwarding operations (mobile-to-mobile, static-to-mobile, mobile-to-static and static-to-static). NetSpray includes a spray phase and a focus phase. In the spray phase, we design a binary-spraying mechanism to spread message copies. In the focus phase, we forward message copies jointly considering delivery predictability, remaining energy and network participation predictability. Aiming to tackle the storage-constrained issue of sensor nodes, a storage management scheme is proposed. The simulation and practical experiments show that NetSpray can fully exploit the message-synchronization capability of WAON, and has better performance than existing forwarding mechanisms in disaster scenarios.